(untitled) (Architecture Image Studies, 2025)
This study empirically investigates the influence of safety perception factors on construction workers’ actual safety behavior. Based on survey data from 225 workers, an ordinary least squares (OLS) multiple regression showed that perceived coworker cooperation (A9; β = 0.30, p < 0.001), supervisor emphasis on safety (A8; β = 0.15, p = 0.001), and recognition of minor hazards (A6; β = 0.15, p = 0.010) significantly and positively predicted the average safety behavior score (B_avg), whereas other perception items, including A2 and A7, were not statistically significant (p > 0.05). The model explained a substantial proportion of variance (R² = 0.79; adjusted R² = 0.78), and five-fold cross-validation indicated robust generalizability (mean R² = 0.75 ± 0.05). All responses were collected anonymously, and a self-administered five-point Likert scale (1 = Strongly Disagree, 5 = Strongly Agree) was used. Mediation analysis further suggested that A6 exerted an indirect effect via A9 (indirect = 0.24, ≈37.4% of the total effect; standardized coefficients with bootstrap 95% confidence intervals reported). These findings provide empirical evidence that organizational culture facilitates the transition from perception to behavior and support a shift from hardware-centered control toward collaboration-oriented culture and value-based education to promote voluntary safety behavior.